THU0100 Disease Characteristics Associated with the Presence of Dactylitis in Patients with Early Spondyloarthritis (SPA): Results from Esperenza Cohort. (10th June 2014) - Tévar Sánchez, M.I.; Navarro-Compán, V.; Almodόvar, R.; Fernández Dapica, M.P.; Zarco, P.; de Miguel, E.
Abstract : Background: Dactylitis is a typical manifestation in SpA patients. Despite dactylitis has traditionally been related to the coexistence of psoriasis and peripheral arthritis, it was included as SpA feature for both (axial and peripheral) ASAS classification criteria. However, data supporting this is scarce, especially in patients with recent onset. Objectives: To determine the prevalence of dactylitis and which are the disease characteristics associated with its presence in patients with early SpA. Methods: Baseline dataset from the EsPeranza cohort (<45 years, symptoms duration 3-24 months and with inflammatory back pain -IBP- or asymmetrical arthritis or spinal/joint pain plus ≥1 SpA features) was analysed. For this study, 609 patients diagnosed of SpA by their physician were included. Logistic regression analysis was employed to investigate the association between disease characteristics and the presence of dactylitis. These characteristics included family history of SpA, clinical manifestations (chronic back pain – CBP, inflammatory back pain – IBP, peripheral arthritis, enthesitis, uveitis, psoriasis, nail lesions, inflammatory bowel disease –IBD – and urethritis or cervicitis), activity parameters (SJC, physician's VAS, patient's VAS and BASDAI), metrology (BASMI), function (BASFI), lab tests (HLA B27, ESR and CRP), and imaging (sacroiliitis on x-Ray or MRI by ASAS definition). Results: Fifty eight (10.5%) patients had current or previous dactylitis. In the univariable analysis, the presence of dactylitis was associated with peripheral arthritis, enthesitis, psoriasis, nail lesions, SJC, physician's VAS and CRP. Moreover, CBP, IBP and sacroiliitis were associated with the absence of dactylitis. No significant differences were found for the rest of variables. In the multivariable analysis, the presence of dactylitis was independetly associated with peripheral arthritis, enthesitis, psoriasis and physician's VAS (Table 1 ). However, 14 (24%) patients did not have peripheral arthritis but had axial symptoms/signs. Further, patients with dactylitis were classified as patients with dactylitis and psoriasis (n=19; 32.8%) and patients with dactylitis and no psoriasis (n=39; 67.2%). Disease characteristics were compared between both groups. Male were more frequent in the group with psoriasis (84% vs 51%;p<0.05). The group without psoriasis had higher frequency of CBP, IBP, enthesitis, HLA-27 and sacroiliitis but these differences did not reach statistical significance. Conclusions: Dactylitis is a frequent manifestation in patients with SpA even at early stages of the disease. Its presence is mainly associated with peripheral manifestations and psoriasis. However, the majority of patients with dactylitis do not have psoriasis and 24% of them have axial manifestations in absence of peripheral arthritis. Acknowledgements: The EsPeranza Program has been supported by an unrestricted grant from Pfizer Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2885